Methodological approaches applicable to patient-provider interaction analysis: A mini-review - Rey Velasco, Elena; Pedersen, Hanne Sæderup; Skinner, Timothy Charles (Frontiers in Communication, 2022)
Online platforms and smartphone applications that facilitate patient-provider communication are examples of how digital technologies support human interaction. Telehealth enables clinical encounters when physical consultations are not possible, and evidence confirms that face-to-face and remote healthcare encounters have comparable efficacy. Furthermore, research shows that patient-provider communication and relationship influence patient outcomes. However, we lack studies on what happens during these interactions, particularly in text-messages conversations, from a linguistic or behavioural perspective. Our research methods shall evolve alongside our communication channels. Currently, there is an overall preference for qualitative methods in patient-provider communication research. Some authors argue that quantitative measures (clinical measurements, questionnaires) lack an understanding of the patients’ experiences, whereas qualitative approaches (interviews, focus groups) provide the full picture. Others suggest their combination to interpret interactions thoroughly. As a result, it is often difficult for a communication researcher to choose between one or more approaches. We conducted a mini-review of qualitative approaches, such as corpus linguistics and conversation analysis, as well as quantitative approaches, such as analysis of variance and temporal pattern detection, for patient-provider communication analysis. Additionally, we distinguish relevant communicative features in synchronous or live interactions, such as video-calls, and asynchronous interactions, such as non-instant messaging. We further discuss these methods’ potential for combination and their applications in digital communication research. We aim to guide researchers to choose a methodology for digital interaction studies. Our recommendations are based on these approaches’ ability to answer a research question, and we suggest a mixed-methods approach in future digital communication research.